PCK1 and SLC22A2 gene variants associated with response to metformin treatment in type 2 diabetes. - Sophie St-Amour; Laurence Tessier; Janie Harnois; Catherine Allard; Alexandre Lavoie; Philippe Caron; Luigi Bouchard; Patrice Perron; Karine Tremblay (PLoS ONE)
Type 2 diabetes (T2D) is a chronic disorder affecting 462 million worldwide, often managed with metformin as first-line treatment. However, metformin's response varies among individuals, including up to 30% experiencing serious adverse drug reactions (ADRs) and 20-50% inefficacy. These differences may be due to various factors, including pharmacogenetic (PGx) variants. The PGx variants documented so far could affect both the safety and efficacy of metformin, but due to a lack of replication studies, none reached the clinical evidence-level needed to be used as a predictive marker for treatment response. Therefore, this study aims to evaluate the association between the presence of candidate PGx variants and metformin response in T2D subjects. We conducted an association study involving 108 T2D participants currently or previously treated with metformin. A characterization of their therapeutic response was carried out through questionnaires and pharmacological profile reviews. DNA samples were collected during their single visit to perform genotyping of 24 selected candidate PGx variants. Association analyses between candidate PGx variants and metformin response were performed. Among the subjects included in the analyses (n =  84), 25% were non-responders, and 58% experienced ADRs. At the time of study enrollment, 93.9% of non-responders continued to use metformin. The odds of being a non-responder to metformin are 5.6 times higher for homozygous carriers of the alternative allele of a variant within the PCK1 gene (rs4810083) compared to the other genotypes (95% interval confidence [1.9-16.6]). Two variants in perfect linkage disequilibrium within the SLC22A2 gene (rs316019 and rs316009) were associated with increase odds of having ADRs, where homozygous genotype carriers are 7.3 times more likely to have ADRs presentation (95% interval confidence [1.85-29.01]). This study identified associations between PCK1 and SLC22A2 candidate PGx variants and metformin response in T2D treatment. Additional genetic and functional studies are necessary to elucidate the variants' impact in metformin's pharmacological mechanisms.